2017
DOI: 10.1017/wsc.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Integrated Weed Management System for Herbicide-Resistant Weeds Using Lentil (Lens culinaris) as a Model Crop

Abstract: The escalating evolution of weed species resistant to acetolactase synthase (ALS)-inhibitor herbicides makes alternative weed control strategies necessary for field crops that are dependent on this herbicide group. A fully integrated strategy that combined increased crop seeding rates (2X or 4X recommended), mechanical weed control with a minimum-tillage rotary hoe, and reduced-rate non–ALS inhibitor herbicides was compared with herbicides, rotary hoe, and seeding rates alone as a method of controlling ALS inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…For beans (Vigna sinensis L.), mechanical and chemical weed control were found to show no significant differences in weed occurrence and yield [27]. A study with lentils (Lens culinaris) concluded that an integrated approach consisting of increased sowing density, mechanical weed control, and reduced herbicide application rate had the same effect on yield and weed suppression as the standard approach of standard sowing density, full herbicide application and no mechanical weed control [28]. In a study with organically cultivated OSR hoeing significantly reduced the number of weeds [29].…”
Section: Introductionmentioning
confidence: 99%
“…For beans (Vigna sinensis L.), mechanical and chemical weed control were found to show no significant differences in weed occurrence and yield [27]. A study with lentils (Lens culinaris) concluded that an integrated approach consisting of increased sowing density, mechanical weed control, and reduced herbicide application rate had the same effect on yield and weed suppression as the standard approach of standard sowing density, full herbicide application and no mechanical weed control [28]. In a study with organically cultivated OSR hoeing significantly reduced the number of weeds [29].…”
Section: Introductionmentioning
confidence: 99%
“…The dose-response work by Redlick et al (2017a) eloquently showed the trade-off between plant densities and herbicides for effective weed management and the importance of plant stand densities for improving herbicide efficacy and reducing the necessity for herbicides for weed management in lentil (Lens culinaris Medik.) (Redlick et al 2017b). Increasing soybean plant densities by 50% above the standard density did not translate into a shortening of the CWFP.…”
Section: Target Density Experimentsmentioning
confidence: 87%
“…Pre-emergence herbicides are effective in controlling weeds early in crop growth, but weeds germinating after crop emergence at the pre-flowering stage pose a threat to lentil production [ 8 ]. Weeds can be controlled using mechanical and manual weeding, soil sterilization, and high seed rate density [ 9 ], but these methods are either inefficient or very expensive [ 10 ]. Post-emergence herbicides like imazethapyr and metribuzin are effective at controlling weeds in many legume crops, including lentils [ 6 , 11 ], chickpeas [ 8 ], and soybeans [ 12 ].…”
Section: Introductionmentioning
confidence: 99%